2018
DOI: 10.1097/pai.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

An Immunoscore Using PD-L1, CD68, and Tumor-infiltrating Lymphocytes (TILs) to Predict Response to Neoadjuvant Chemotherapy in Invasive Breast Cancer

Abstract: Response to neoadjuvant chemotherapy (NAC) in invasive breast cancer (IBC) is partly regulated by the immune microenvironment. We evaluated immune checkpoint PD-L1 expression, presence of CD68+ cells of macrophage/monocytic lineage and stromal tumor-infiltrating lymphocytes (TILs) in prechemotherapy biopsies and correlated with NAC response. We studied 76 cases of IBC. Prechemotherapy biopsies with >30% TILs were considered lymphocyte-rich IBC. We performed immunohistochemistry for PD-L1 and CD68. Prechemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
2
12
0
1
Order By: Relevance
“…Out of all different subtypes of BC, TNBC and HER2 + BCs are identified to have a significant association with the immune surveillance of the host [19,22]. These studies also highlight the significance of immunomodulation, the number of tumor-infiltrating lymphocytes, and the expression of programmed death-ligand (PD-L1) to the disease prognosis and treatment outcome pertaining to human BC [16,[22][23][24]. All these findings emphasize the importance of further investigating the applicability of immunotherapy for HER2 + BC.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Out of all different subtypes of BC, TNBC and HER2 + BCs are identified to have a significant association with the immune surveillance of the host [19,22]. These studies also highlight the significance of immunomodulation, the number of tumor-infiltrating lymphocytes, and the expression of programmed death-ligand (PD-L1) to the disease prognosis and treatment outcome pertaining to human BC [16,[22][23][24]. All these findings emphasize the importance of further investigating the applicability of immunotherapy for HER2 + BC.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies evaluate the importance of PD-1/PD-L1 expression on tumor cells and/or immune cells and the presence of TILs and Tregs in the tumor microenvironment in predicting response to treatment pertaining to BC [3,104,108,113,114]. Specifically, blocking immune evasion and attracting more TILs and fewer Tregs (reactivating immunogenicity of BC) to the tumor microenvironment can improve the OS of BC patients [19,23,[115][116][117][118][119]. Sixteen percent of HER2 + subtypes are lymphocyte predominant (> 50-60% of TILs present) and are associated with improved outcome (EFS: event-free survival, OS) with many treatment modalities [19,[120][121][122][123][124].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…65 This system has been used extensively in hepatocellular carcinoma, melanoma, colorectal, high-grade serous ovarian, invasive breast and gastric cancer. [66][67][68][69][70][71][72][73][74][75][76] By routinely calculating an Immunoscore at the time of diagnosis prior to treatment with immune therapy, we may find that the Immunoscore can predict responses to checkpoint inhibition.…”
Section: Immunoscore In Non-cns Malignanciesmentioning
confidence: 99%
“…FANG LIU 1,2,6* , BENOÎT SANSAS 3* , XAVIER PRÉVILLE 3,7 , ROMAIN GINESTE 1,2,8 , JIALEI WANG 4,5 , HUI YU 4,5 , XIA MENG 1,2 , ROMAIN MICOL 3,9 and LUC BARRAUD 3 studies demonstrated that the immune status of the patient is crucial, as it may affect treatment outcome (7,8). In addition, recent studies demonstrated that chemotherapy clearly affects immune effectors, such as PD-L1 expression and/or tumor-infiltrating lymphocyte (TIL) infiltration (9,10).…”
Section: Elevated Il-6/il-1ra Ratio As a Prognostic Biomarker Of Poormentioning
confidence: 99%